2020
DOI: 10.1002/ijgo.13508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS‐CoV‐2 on multiple gestation pregnancy

Abstract: The incidence of multiple pregnancies varies in different populations and countries. Twinning rates in India are reported to be below 9 per 1000 births. 1 As of October 20, 2020 SARS-CoV-2 (COVID-19) had affected approximately 40 million individuals globally and caused more than 1 million deaths, 2 including many pregnant women with twin gestation. Multiple gestational pregnancies (MGP) are associated with a high risk of both fetal and maternal complications and require

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
(20 reference statements)
0
7
0
4
Order By: Relevance
“…However, these reported studies have yielded conflicting findings leading to contradictory conclusions. Some reports indicate that there are no major adverse outcomes of SARS‐CoV‐2 infection in pregnancy, 4,5 others have reported serious pregnancy complications such as preterm births, neurological disorders, miscarriages, and maternal deaths in women infected with SARS‐COV2 during pregnancy 6‐13 . Multiple systematic reviews have been conducted that have majorly described the risk of vertical transmission and maternal presentation associated with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…However, these reported studies have yielded conflicting findings leading to contradictory conclusions. Some reports indicate that there are no major adverse outcomes of SARS‐CoV‐2 infection in pregnancy, 4,5 others have reported serious pregnancy complications such as preterm births, neurological disorders, miscarriages, and maternal deaths in women infected with SARS‐COV2 during pregnancy 6‐13 . Multiple systematic reviews have been conducted that have majorly described the risk of vertical transmission and maternal presentation associated with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Gurol-Urganci and colleagues [ 32 ] showed a higher risk of pre-eclampsia in SARS-CoV-2-infected patients in their study (3.9%; p < 0.001). Mahajan et al [ 33 ] evaluated the effect of COVID-19 on multiple gestation pregnancies. Based on their study, the risk of pre-eclampsia/eclampsia was higher in MGPs with COVID-19 than MGPs before the pandemic (50.0% vs. 12.7%) and singleton pregnancies (41.6% vs. 7.9%).…”
Section: Resultsmentioning
confidence: 99%
“…A similar increased rate of severe disease and maternal mortality has been recently reported in the American population, suggesting that pregnant women should be considered a high-risk population for COVID-19 until proven otherwise [ 11 ]. It has been previously reported that infected women with twin gestations did not present with severe disease as compared to their singleton counterparts [ 12 ]. Our study had three twins and their mothers did not experience severe disease.…”
Section: Discussionmentioning
confidence: 99%